Vitamin D Status in Madura Pregnant Women with Hypertension: A Case Control Study - Setiarsih, Dini; Hastuti, Pramudji; Nurdiati, Detty Siti; Putri, Lidia Aditama (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Vitamin D deficiency is inversely related to blood pressure and may contribute to the genesis and maintenance of hypertension. However, in many clinical studies the relationship between vitamin D status and blood pressure has not shown consistent results. This study aims to analyze differences in vitamin D status in Madurese ethnic pregnant women with hypertension and non-hypertension. Subjects and Method: This research is an analytical observational design with a case control study. The target population in this study were pregnant women who came from the Madurese ethnicity. The affordable population is pregnant women who come from the Madurese ethnicity in the Work Area of the Bangkalan District Health Office. The study was conducted in the period from May 2018 to February 2020. The sampling technique used was consecutive sampling. The sample size was 105 pregnant women with hypertension and 105 controls. The independent variables included consumption of food sources of vitamin D and exposure to ultraviolet B rays. The dependent variable was vitamin D levels. Data on consumption of foods that were sources of vitamin D was obtained using the Food Frequency Questionnaire (FFQ). Data on exposure to ultraviolet B (UV B) rays were obtained by questionnaire. Data on vitamin D levels were obtained from the collection of blood serum which was then analyzed by ELISA Kit. Independent Sample T and chi square test were used to analyze the differences in variables between the two groups. Results: The mean value of vitamin D levels in the case and control groups were 37.87 ng/mL and 37.89 ng/mL, respectively. Subjects with vitamin D insufficient status were more in the case group (19.00%) than the control group (16.20%). The results showed that there was no significant difference between the two groups in vitamin D levels (p= 0.984) and vitamin D status (p= 0.587). Insufficient exposure to UV B provides a 3.95 times greater risk of experiencing insufficient vitamin D. Conclusion: The conclusion of this study is that the role of vitamin D in the incidence of hypertension in pregnancy has not been determined.